Increased pretransplantation plasma kynurenine levels do not protect from but predict acute kidney allograft rejection - Lahdou, Imad; Sadeghi, Mahmoud; Daniel, Volker; Schenk, Martin; Renner, Fabrice; Weimer, Rolf; Löb, Stefan; Schmidt, Jan; Mehrabi, Arianeb; Schnitzler, Paul; Königsrainer, Alfred; Döhler, Bernd; et al. (Human immunology, 2010)
Indoleamine 2,3-dioxygenase (IDO), an enzyme expressed in many cell types, catalyses degradation of tryptophan (Trp) to kynurenine (Kyn) and may exert immunosuppressive functions, mediated mainly by kynurenines. Therefore, increased Kyn concentrations would be expected to protect allografts from rejection. We conducted this study to examine whether Kyn has predictive value for kidney graft outcome. End-stage renal disease patients (n = 210) demonstrated an increased Kyn/Trp ratio compared with healthy controls (n = 30). Both Kyn and Trp levels were significantly higher in patients who subsequently developed acute rejection than in patients who did not (p < 0.001 and p < 0.001, respectively). Furthermore, pretransplantation Kyn and Trp plasma concentrations were significantly different in patients who went on to develop acute rejection (high values) or acute tubular necrosis (low values) (p = 0.007 and p = 0.021, respectively). After transplantation Kyn levels decreased. Approximately 3 days before biopsy-confirmed rejection, Kyn was significantly increased in patients with rejection compared with those without rejection (p < 0.001). Contrary to expectation, high Kyn plasma levels before transplantation were not predictive of low rejection risk. Although informative in overall terms, at the present stage, Kyn levels do not allow the concise risk differentiation of individual patients.